A supramolecular glass made from a low molecular weight amino acid derivative. (5th January 2022) - Baker, B.C.; O'Donnell, A.D.; Priya,; Hyder, M.; German, I.M.; Hayes, W.
Graphical abstract: Highlights: A nitro-aromatic urea derivative of tyrosine assembles into a novel bio-derived glass. The molecular transparent glass can be reprocessed via either solution or melt casting. Supramolecular assembly was assessed via variable-temperature infrared spectroscopy. Abstract: A low molecular weight tyrosine derivative with self-assembling capabilities has been found to form a robust optically transparent supramolecular glass after casting at 70 °C. The glass films are remarkably stable, remaining transparent over 12 + months as well as in contact with water and can be reprocessed via solvation in a wide range of organic solvents. The solubility, long-term stability and thermo-responsive properties of the bio-derived glass makes it an ideal candidate for use as a window where its reprocessability at easily accessible temperatures are attractive.